2015
DOI: 10.5897/jdoh2015.0150
|View full text |Cite
|
Sign up to set email alerts
|

Quality of root canal filling performed by undergraduate students in a Saudi Dental College

Abstract: The aim of this study was to evaluate the outcomes of teaching endodontics to undergraduate students at Riyadh Colleges. This study was undertaken by assessing the technical quality of root canal obturation and the presence of procedural errors in root canal treatment cases performed by the final year dental students in clinics. All of the root canal treatment cases performed by the final year dental students in the 2nd semester of 2012 to 2013 were examined, with a total of 450 root canals from 241 teeth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
4
3
0
Order By: Relevance
“…These results are close to those reported by Er et al [8], AlRahabi et al [11], Elsayed et al [41], AbuMstafa et al [34], and Roman-Richon et al [14]. By tooth type, tapering problems were higher in molars teeth which similar to some previous studies [11, 18, 34]. By root canal location, mesiolingual, mesiobuccal, and distobuccal canals were the most subjected to shaping errors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are close to those reported by Er et al [8], AlRahabi et al [11], Elsayed et al [41], AbuMstafa et al [34], and Roman-Richon et al [14]. By tooth type, tapering problems were higher in molars teeth which similar to some previous studies [11, 18, 34]. By root canal location, mesiolingual, mesiobuccal, and distobuccal canals were the most subjected to shaping errors.…”
Section: Discussionsupporting
confidence: 92%
“…Although with no significant difference, the quality of length in the mandible was higher than that in the maxilla. This result is similar to that reported by Moradi & Gharechahi [28] while, it contradicts the results reported by Elsayed et al [41], AbuMostafa et al [34], and Elemam et al [18], who reported higher quality in the maxilla with significant difference. These variations might due to the difference in the evaluation criteria, teaching methods, and/or type of the study sample (clinical vs. preclinical).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, methodological flaws could have been introduced due to the inherent limits of radiographic evaluation and interpretation, as the radiographic appearance may be impacted by changes in beam and film angulation [ 5 ]. The overall quality of endodontic treatment could be influenced by the type of instrumentation and obturation technique as most undergraduate training employ conventional stainless-steel hand files with step-back and cold lateral condensation techniques [ 11 , 30 ]. Nevertheless, stringent documentation standards and continuing dental education are warranted to guarantee that dental students adhere to ethical conduct and are conversant with institutional documentation policies.…”
Section: Discussionmentioning
confidence: 99%
“…Several root canal filling audits have been conducted among dental students by examining radiographs taken during clinical practice and comparing them to pre-determined benchmarks [5,[8][9][10]. However, the available findings revealed mixed results on the acceptability of root canal obturation performed by dental students ranging from 36% to 80.2% [8][9][10][11]. Nonetheless, these studies were conducted before the outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), known as COVID-19.…”
Section: Introductionmentioning
confidence: 99%